Remoção de matéria orgânica e nutrientes em sistema de tanque séptico seguido de wetland construído de fluxo vertical com recirculação - Ramírez, Rolando José Manuel González (2019)
The aim of this study was to evaluate the performance of a domestic wastewater treatment system in full scale with septic tank (ST) followed by vertical down-flow constructed wetland (VDCW), planted with Canna x generalis, operating with recirculation, in removal of carbonaceous organic matter, solids, nitrogen and phosphor in the treatment of the inlet wastewater. The ST (V = 4,7 m3) was used in the primary treatment, and the VDCW (24.5 m2 surface area) was used in the secondary treatment of domestic wastewater. Over a period of 360 days (01/05/18 – 25/04/19), operating with 1200 L d-1 raw domestic wastewater inlet, recirculation rate of 90% and average loads of 882 gBOD d-1, 1417 gCOD d-1, 1246 gSS d-1, 1890 gST d-1, 83 gNH4+-N d-1, 150 gTN d-1 and 13 g PO43--P d-1, the system (ST/VDCW) showed high average organic matter removals (85% BOD, 86% COD), suspended solids (93%), ammonia nitrogen (80% NH4+-N); good removal of total solids (65%) and total nitrogen (67% TN). However, the system proved inefficient in removing inorganic phosphorus (PO43--P). TS stood out for its high 88% NO3--N removal for 21 g NO3--N d-1 average inlet load, providing conditions for the denitrification process. The VDCW, with a average HLR of 90 mm d-1 and average loads of 32 gBOD m-2 d-1, 66 gCOD m-2 d-1, 60 gSS m-2 d-1, 97 gTS m-2 d-1, 4 gNH4+-N m-2 d-1 and 7 gTN m-2 d-1, showed average removal efficiencies of 67%, 76%, 88%, 45%, 70% and 45% for BOD, COD, SS, TS, NH4+-N and TN respectively. Canna x generalis showed good adaptation and rapid growth, contributing with 10% of the removal of TN from VDCW after cutting its biomass. From hydrodynamic tests with rhodamine tracer WT, variations in VDCW hydraulic behavior were observed, and an average percolation time of 18 min was determined. Vegetation growth showed a variable correlation, from weak to strong, with wetland percolation time over time, indicating possible influence of water interception by the aerial part of the plant and pore obstruction and formation of preferential paths in the filter bed, due to the spreading and growth of roots and rhizomes. The removal of NO3--N in ST was associated with the high abundance of heterotrophic denitrifying bacteria found in the accumulated sludge, which showed seasonal variation in diversity and relative abundance, with the predominant genus being Acidovorax, Rhodopseudomonas, Paracoccus and Pseudomonas. In VDCW, high NH4+-N removal was associated with the presence of autotrophic AOB (Nitrosomonas, Nitrosospira) and NOB (Nitrobacter, Nitrospira) found throughout the depth of the filter bed and also adhered to the roots of the vegetation, with seasonal variation of diversity and abundance. In the filter bed, an abundance of anaerobic bacteria of the genus Clostridium and denitrifying bacteria of the genus Flavobacterium, Pseudomonas, Acinetobacter has been found; indicating significant formation of anaerobic microenvironments, and associated with good TN removal, indicates the possible occurrence of simultaneous nitrification and denitrification processes in VDCW.